Reaction of indoles with aromatic fluoromethyl ketones: an efficient synthesis of trifluoromethyl(indolyl)phenylmethanols using K2CO3/n-Bu4PBr in water - Pillaiyar, Thanigaimalai; Sedaghati, Masoud; Schnakenburg, Gregor (Beilstein Journal of Organic Chemistry, 2020)
A new, mild and efficient protocol for the synthesis of trifluoromethyl(indolyl)phenylmethanols by the reaction of indoles with a variety of aromatic fluoromethyl ketones in the presence of K2CO3 (15 mol %) and n-Bu4PBr (15 mol %) in water. The desired products were obtained in good to excellent yields without requiring a column chromatographic purification. The reusability of the catalytic system and large-scale synthesis of indolyl(phenyl)methanols, which would further transform into biological active indole-derived compounds, are further advantages of this protocol.
Keywords: C–C-bond formation; C3-funtionalization of indole; diindolylmethane; Friedel–Crafts reaction; indole; indole-3-carbinol; large-scale synthesis; recyclability

(untitled) - Mei, G.-J.; Shi, F. (J. Org. Chem., 2017)

(untitled) - Li, X.; Tan, W.; Gong, Y.-X.; Shi, F. (J. Org. Chem., 2015)

(untitled) - Tan, W.; Du, B.-X.; Li, X.; Zhu, X.; Shi, F.; Tu, S.-J. (J. Org. Chem., 2014)

(untitled) - Liu, Y.; Zhang, H.-H.; Zhang, Y.-C.; Jiang, Y.; Shi, F.; Tu, S.-J. (Chem. Commun., 2014)

(untitled) - He, Y.-Y.; Sun, X.-X.; Li, G.-H.; Mei, G.-J.; Shi, F. (J. Org. Chem., 2017)

(untitled) - Inamdar, S. M.; Gonnade, R. G.; Patil, N. T. (Org. Biomol. Chem., 2017)

(untitled) - Xiao, J.; Wen, H.; Wang, L.; Xu, L.; Hao, Z.; Shao, C.-L.; Wang, C.-Y. (Green Chem., 2016)

(untitled) - Suárez, A.; Martínez, F.; Sanz, R. (Org. Biomol. Chem., 2016)

(untitled) - Wen, H.; Wang, L.; Xu, L.; Hao, Z.; Shao, C.-L.; Wang, C.-Y.; Xiao, J. (Adv. Synth. Catal., 2015)

(untitled) - Pillaiyar, T.; Gorska, E.; Schnakenburg, G.; Müller, C. E. (J. Org. Chem., 2018)

(untitled) - Deb, M. L.; Das, C.; Deka, B.; Saikia, P. J.; Baruah, P. K. (Synlett, 2016)

(untitled) - Jadhav, S. D.; Singh, A. (J. Org. Chem., 2016)

(untitled) - Lancianesi, S.; Palmieri, A.; Petrini, M. (Adv. Synth. Catal., 2012)

(untitled) - Sun, F.-L.; Zheng, X.-J.; Gu, Q.; He, Q.-L.; You, S.-L. (Eur. J. Org. Chem., 2010)

The Health Professional's Guide to Popular Dietary Supplements - Sarubin-Fragakis, A.; Thomson, C. (American Dietetic Association, 2007)

(untitled) - Park, N. I.; Kim, J. K.; Park, W. T.; Cho, J. W.; Lim, Y. P.; Park, S. U. (Mol. Biol. Rep., 2011)

(untitled) - Okulicz, M.; Hertig, I.; Chichłowska, J. (Czech J. Anim. Sci., 2009)

(untitled) - Sarver, P. J.; Bacauanu, V.; Schultz, D. M.; DiRocco, D. A.; Lam, Y.-h.; Sherer, E. C.; MacMillan, D. W. C. (Nat. Chem., 2020)

Organofluorine compounds in biology and medicine - Reddy, V. P. (Elsevier, 2015)

Modern fluoroorganic chemistry: Synthesis, reactivity, applications - Kirsch, P. (Wiley-VCH, 2013)

Organofluorine Chemistry - Uneyama, K. (Blackwell Publishing, 2006)

(untitled) - O’Hagan, D. (J. Fluorine Chem., 2010)

(untitled) - Jiang, H.-X.; Zhuang, D.-M.; Huang, Y.; Cao, X.-X.; Yao, J.-H.; Li, J.-Y.; Wang, J.-Y.; Zhang, C.; Jiang, B. (Org. Biomol. Chem., 2014)

(untitled) - Bandini, M.; Sinisi, R. (Org. Lett., 2009)

(untitled) - Liu, X.-D.; Wang, Y.; Ma, H.-Y.; Xing, C.-H.; Yuan, Y.; Lu, L. (Tetrahedron, 2017)

(untitled) - Hua, Y.-Z.; Chen, J.-W.; Yang, H.; Wang, M.-C. (J. Org. Chem., 2018)

(untitled) - Safrygin, A. V.; Irgashev, R. A.; Barabanov, M. A.; Sosnovskikh, V. Y. (Tetrahedron, 2016)

(untitled) - Wang, Y.; Yuan, Y.; Xing, C.-H.; Lu, L. (Tetrahedron Lett., 2014)

(untitled) - Pillaiyar, T.; Köse, M.; Sylvester, K.; Weighardt, H.; Thimm, D.; Borges, G.; Förster, I.; von Kügelgen, I.; Müller, C. E. (J. Med. Chem., 2017)

(untitled) - Pillaiyar, T.; Dawood, M.; Irum, H.; Müller, C. E. (ARKIVOC, 2018)

(untitled) - Pillaiyar, T.; Uzair, M.; Ullah, S.; Schnakenburg, G.; Müller, C. E. (Adv. Synth. Catal., 2019)

(untitled) - Ling, Y.; An, D.; Zhou, Y.; Rao, W. (Org. Lett., 2019)

(untitled) - Sasaki, S.; Ikekame, Y.; Tanayama, M.; Yamauchi, T.; Higashiyama, K. (Synlett, 2012)

(untitled) - Muthukumar, A.; Sekar, G. (J. Org. Chem., 2018)